INTRA INTRA-SCHOOL STUDENT ORGANIZATIONS AS A STRATEGY FOR SHAPING STUDENT CHARACTER AT DARUL HIKMAH ISLAMIC SENIOR HIGH SCHOOL MOJOKERTO - Sugiantoro, Heri; Masnawati, Eli (International Journal of Multidisciplinary Reseach, 2025)
Education is an important indicator that determines the direction of a good nation so that the nation's goals are achieved as stated in the Constitution, namely to educate the nation's life can be implemented properly. This study aims to describe the role of the Intra-School Student Organization (OSIS) in shaping the character of students at MA Darul Hikmah Mojokerto in the 2025–2026 academic year. The background of this service departs from the phenomenon of declining student character marked by violations of school rules, religious norms, and social norms. This service uses the PAR (Participatory Action Research) method. This method is a method that involves certain parties in reviewing actions that are in order to make better changes and improvements showing that OSIS has an important role in character formation through four main programs, namely the School Environment Introduction Period (MPLS), Classmeeting, Basic Student Leadership Training (LDKS), and Deliberation/Evaluation. These four activities have been proven to be able to instill the values ​​of discipline, responsibility, care, cooperation, tolerance, leadership, and courage in expressing opinions. The Student Council (OSIS) also serves as a preventative measure to prevent deviant student behavior by providing space for the development of creativity, democratic attitudes, and solidarity. Thus, the OSIS at MA Darul Hikmah Mojokerto serves not only as a student organization but also as a strategic instrument for positive character formation, personality strengthening, and the comprehensive development of the potential of the younger generation.